PICARD 2012 (2013)
Reports on the annual conference which is organised by WCO to faciliate partnership and provide a venue for Customs officials and academics to network and exchange ideas and research findings. Reveals that the 2012 meeting focused on three main topics viz., the impact of regional economic integration and preferential trade arrangements on Customs services, emerging and evolving risks and Customs strategic human resource management.
Keywords: CUSTOMS